Rancang Bangun Solar Water Heater (SWH) Jenis Pelat Datar dengan Pemrograman Arduino UNO - Raharjo, Adib budi; , Dr. Agus Ulinuha, ST. MT, Ph.D (2017)
Solar energy is one of the alternative energy with low-risk of pollution. The usage of solar energy has spread on many fields in practical. Until this days, so many inovations that are using solar energy as solution of some problems. But, all things that related to solar energy usage, still need high-cost of production. In this research, the focus aims to create a device that is using solar energy with low-cost, which is creating a water heater. The water heater that was made in this research, is not using complicated electronic components, this metal plate is made from copper that has length 15 meters and its diameter is 0.5 inches. In the operation of this heater, it uses microcontroller based on Arduino UNO. This microcontroller activates the water pump and the automatic valve with dc motor as the actuator. The usage of this heater, fully depends on sun radiation in passive system. This heater yields hot water with temperature above 45 degree celcius. We will get 1.5 liters of hot water at one time of filling. And the hot water tank is made from stainless steel with volume of 50 liters in total. This will be one of the solution for daily needs of hot water, because the majority of water heater device on market is expensive and causing polutions. Keywords : water heater, arduino UNO, solar energy, motor DC.